Effect of Drying Techniques on Nutrition Content and Gross Energy of Nuabosi Cassava (Manihot esculenta) Flour - Melania Priska; Natalia Peni; Ludovicus Carvallo; Veronika P. S. M. Wae (Biosaintifika: Journal of Biology & Biology Education, 2020)
This reseach aimed to determine the proper cassava drying technique to produce suitable flour properties for food product applications. The method used was proximate analysis and calculation of Gross Energy (GE) value. Furthermore, the results of the study were analyzed using the Two Way ANOVA statistical test followed by the real difference test using the Tukey analysis. Results of the analysis showed that there was no significant difference between the two drying techniques (Î±0.05). To get good quality flour in the application of food products made from Nuabosi cassava flour is to use oven drying and sun drying techniques. The novelty of this study is that there has been no previous research on the quality of Nuabosi cassava flour using oven drying and sun drying techniques. The benefit of this research is to support the government in the food diversification program on foods made from Nuabosi cassava flour, where Nuabosi cassava is one of the leading types of food in Ende district.